Functionally Graded Structures: Modelling and Computation of Static and Dynamical Problems - Chakraverty, Snehashish; Kumar Jena, Subrat; Civalek, Ömer (Institute of Physics Publishing, 2023)
This book explores the static and dynamical behaviours such as bending, buckling, and vibration of functionally graded structures using existing and new theories. The text presents a holistic examination of functionally graded structures, providing invaluable knowledge for professionals, researchers, and educators alike, while contributing significantly to the advancements of the said challenging field.